Global electronic commerce: Tax issues - Kasipillai, Jeyapalan; Saleh, Abdul Razak (1999)
The sudden surge in the use of electronic commerce has facilitated the communication and exchange of information at an unprecedented level.Although the brisk development of e-commerce is more apparent in developed countries, Malaysia is not far behind.E-commerce is the symbiotic integration of communications, data management, and security capabilities to allow business applications within different organizations to automatically exchange information related to the sale of goods and services. E-commerce, therefore, combines the advantages of computer-based processing (speed, reliability. and relatively high volumes of data) with the advantages of people-based insight (creativity, flexibility and adaptability).E-commerce also enables entrepreneurs to review, analyze. add value, and sell a variety of - products that are represented electronically, such as reference material, textbooks and training materials, and computer sofware.The World Trade Organization (WTO) has reported that 51 percent of global trade was transacted through facsimile and telephone while 17 percent was conducted through the lnternet and the balance by other means.The WTO further estimated that global revenues from Internet commerce could be USS2OO billion a year by the turn of the century and grow briskly after that.By the year 2005, one billion people are expected to be on-line (NST, 1998).A preliminary survey conducted by the authors in the northern region of West Malaysia shows that most consumers and retailers arc aware of the use of lnternet for the purposes of commerce.About 60 percent of the consumers expressed their concern regarding the Internet security issue such as possible fraud, security infraction, counterfeiting, and privacy issues. This paper examines how electronic commerce would have an impact on the Malaysian income tax system.Since e-commerce would be an important 'trade route' in the next millenium, tax administrators need to be concerned of the possible loss of revenue due to competition among countries. Moreover, electronic forms of money would provide opportunities and even loopholes for tax evasion.Tax authorities all over the world. therefore, will have to realise that traditional tax rules may have to be modified or adjusted to take account of borderless commerce.